2004
DOI: 10.1158/0008-5472.can-04-1430
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and In vivo Models Analyzing von Hippel-Lindau Disease-Specific Mutations

Abstract: Mutations in the von Hippel-Lindau (VHL) tumor suppressor gene cause tissue-specific tumors, with a striking genotype-phenotype correlation. Loss of VHL expression predisposes to hemangioblastoma and clear cell renal cell carcinoma, whereas specific point mutations predispose to pheochromocytoma, polycythemia, or combinations of hemangioblastoma, renal cell carcinoma, and/or pheochromocytoma. The VHL protein (pVHL) has been implicated in many cellular activities including the hypoxia response, cell cycle arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 42 publications
6
52
0
1
Order By: Relevance
“…These findings were surprising, but are in concordance with observations made by Carmeliet et al 129 who showed that HIF-1a-deficient teratocarcinomas had a growth advantage compared to wild type. However, growth suppression in VHLÀ/À teratocarcinomas may not be entirely dependent on HIF-1, as introduction of a mutated pVHL species (Y112H) into the VHLÀ/À background remained growth suppressive despite restoration of HIF-a regulation, 130 suggesting HIF-independent functions of pVHL in this model.…”
Section: Vhl Phenotypes In Non-renal Tissues: Is It All Hif?mentioning
confidence: 83%
“…These findings were surprising, but are in concordance with observations made by Carmeliet et al 129 who showed that HIF-1a-deficient teratocarcinomas had a growth advantage compared to wild type. However, growth suppression in VHLÀ/À teratocarcinomas may not be entirely dependent on HIF-1, as introduction of a mutated pVHL species (Y112H) into the VHLÀ/À background remained growth suppressive despite restoration of HIF-a regulation, 130 suggesting HIF-independent functions of pVHL in this model.…”
Section: Vhl Phenotypes In Non-renal Tissues: Is It All Hif?mentioning
confidence: 83%
“…52 Introduction of pVHL mutations (Y98N, Y112N, W117R, and R167Q) that are associated with a high risk of renal carcinoma (type 2B) into VHL-deficient cell lines leads to increased normoxic HIF-1a and HIF-2a stabilization compared to wildtype VHL. 57,58 Cells harboring these mutations also display increased proliferation in serum-depleted media and growth in orthotopic xenograft assays, which can be reversed by shRNA-mediated knock down of HIF-2a. 57 The R167Q mutation, in particular, uniquely disrupts regulation of HIF-2a in ES cells.…”
Section: Role In Tumorigenesismentioning
confidence: 99%
“…57 The R167Q mutation, in particular, uniquely disrupts regulation of HIF-2a in ES cells. 58 In contrast, type 2A mutations (Y98H, Y112H, A149T, and T157I), which have a lower risk for renal tumors, display reduced levels of normoxic HIF-a accumulation and growth in xenograft assays compared to type 2B mutants. 57 In contrast to tumor-associated VHL mutations, the R200W mutation in pVHL leads to Chuvash polycythemia, a heritable disease characterized by elevated levels of serum Epo and VEGF.…”
Section: Role In Tumorigenesismentioning
confidence: 99%
“…Control tissues included EBER-positive Hodgkin lymphoma for LMP1, and renal cell carcinoma tissue for HIF-1a and CD31. Additional controls were renal cell carcinoma cell line pellets (RCC4 2-1 over expresses HIF-1a while RCC4 3-14 does not) that were fixed in formalin and paraffin embedded [17]. Specificity was assured in all specimens by parallel stains omitting the primary antibody.…”
Section: Case Selectionmentioning
confidence: 99%